Behaviour of Reinforced Concrete Slabs with Embedded Polystyrene Spheres - Ling, Jen Hua; Lau, Ji Wei; Lim, Yong Tat (Civil and Sustainable Urban Engineering, 2024)
Polystyrene spheres can be used to substitute concrete in reinforced concrete slabs. Despite the weight, the structural performance of the slab would also be affected. This study investigated the behaviour of slabs containing polystyrene spheres under loads. Six specimens were fabricated and tested under the four-point load setup. The parameters studied included the diameters of the polystyrene spheres and the spacing between them. The polystyrene spheres reduced the slabs’ first crack load, stiffness, yield strength, and ultimate strength. The first crack, yield, and ultimate loads decreased by 22.3%, 2.1%, and 4.1%, respectively, when the polystyrene sphere’s diameter increased from 75 mm to 125 mm. As the polystyrene spheres’ spacing decreased from 50 mm to 10 mm, the first crack, yield, and ultimate loads dropped 14.2%, 9.2%, and 7%, respectively. Despite some limitations identified during the feasibility analysis, specimen SP3 was found feasible as a simply supported one-way spanning slab. In the specimen, the polystyrene spheres were 0.625 times the slab thickness in diameter and 2.5 times the concrete cover in spacing.